Dual assessment of kidney perfusion and pH by exploiting a dynamic CEST-MRI approach in an acute kidney ischemia-reperfusion injury murine model - Irrera, Pietro; Consolino, Lorena; Cutrin, Juan Carlos; Zöllner, Frank G.; Longo, Dario Livio (NMR in biomedicine, 2020)
Several factors can lead to acute kidney injury, but damage following ischemia and reperfusion injuries is the main risk factor and usually develops into chronic disease. MRI has often been proposed as a method with which to assess renal function. It does so by measuring the renal perfusion of an injected Gd-based contrast agent. The use of pH-responsive agents as part of the CEST (chemical exchange saturation transfer)-MRI technique has recently shown that pH homeostasis is also an important indicator of kidney functionality. However, there is still a need for methods that can provide more than one type of information following the injection of a single contrast agent for the characterization of renal function. Herein we propose, for the first time, dynamic CEST acquisition following iopamidol injection to quantify renal function by assessing both perfusion and pH homeostasis. The aim of this study is to assess renal functionality in a murine unilateral ischemia-reperfusion injury model at two time points (3 and 7 days) after acute kidney injury. The renal-perfusion estimates measured with iopamidol were compared with those obtained with a gadolinium-based agent, via a dynamic contrast enhanced (DCE)-MRI approach, to validate the proposed method. Compared with the contralateral kidneys, the clamped ones showed a significant decrease in renal perfusion, as measured using the DCE-MRI approach, which is consistent with reduced filtration capability. Dynamic CEST-MRI findings provided similar results, indicating that the clamped kidneys displayed significantly reduced renal filtration that persisted up to 7 days after the damage. In addition, CEST-MRI pH imaging showed that the clamped kidneys displayed significantly increased pH values, reflecting the disturbance to pH homeostasis. Our results demonstrate that a single CEST-MRI contrast agent can provide multiple types of information related to renal function and can discern healthy kidneys from pathological ones by combining perfusion measurements with renal pH mapping.
Gesehen am 16.09.2020